A Case Report of Iatrogenic Pulmonary Artery Injury due to Chest-Tube Insertion Repaired under Cardiopulmonary Bypass. (11th September 2013) - Gabriel, Ciss Amadou; Adama, Dieng Papa; Salmane, Ba Papa; Magaye, Gaye; Souleymane, Diatta; Mohamed, Leye; Lamine, Fall; Birame, Sene Etienne; Assane, N'diaye; Oumar, Diarra; Oumar, Kane; Mouhamadou, N'diaye
Abstract : The authors presented a case of a 50-year-old patient with multiple trauma who suffered from the inadvertent cannulation of the main pulmonary artery at the second attempt of left chest drainage. Pulmonary artery injury has been suspected because early chest tube production was 2300 mL of blood. CT scan showed injury of the trunk of the pulmonary artery, left hemothorax, and suspect damage of the right branch of the pulmonary artery. That chest tube touched the posterior wall of ascending aorta. Surgical approach was median sternotomy. Exploration showed a perforation of the trunk of pulmonary artery without lesion of the right pulmonary branch and the posterior wall of the ascending aorta. The lesion was repaired under normothermic partial cardiopulmonary bypass. Postoperative period was free of events. Review of the literatures for this rare case report has been done.